2021
DOI: 10.1002/eap.2338
|View full text |Cite
|
Sign up to set email alerts
|

Reducing persecution is more effective for restoring large carnivores than restoring their prey

Abstract: Large carnivores are currently disappearing from many world regions because of habitat loss, prey depletion, and persecution. Ensuring large carnivore persistence requires safeguarding and sometimes facilitating the expansion of their populations. Understanding which conservation strategies, such as reducing persecution or restoring prey, are most effective to help carnivores to reclaim their former ranges is therefore important. Here, we systematically explored such alternative strategies for the endangered P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 71 publications
(104 reference statements)
0
26
0
Order By: Relevance
“…Ensuring sufficient habitat remains or is restored in agricultural landscapes will be vital to promote functional connectivity, but this is only half the battle. Connectivity may be overestimated if negative human-wildlife interactions (such as crop foraging or hunting) are not considered (Day et al 2020;Ghoddousi et al 2020;Bleyhl et al 2021). Our sensitivity analysis suggests changes in mortality risk during dispersal are likely to have a large effect on the ability of the agricultural landscape to support orangutan and allow movement between patches.…”
Section: Discussionmentioning
confidence: 96%
“…Ensuring sufficient habitat remains or is restored in agricultural landscapes will be vital to promote functional connectivity, but this is only half the battle. Connectivity may be overestimated if negative human-wildlife interactions (such as crop foraging or hunting) are not considered (Day et al 2020;Ghoddousi et al 2020;Bleyhl et al 2021). Our sensitivity analysis suggests changes in mortality risk during dispersal are likely to have a large effect on the ability of the agricultural landscape to support orangutan and allow movement between patches.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, mitigation of human–leopard conflict should be a conservation priority (Ghoddousi et al, 2020). A recent analysis of metapopulation dynamics of Persian leopard found that reducing levels of persecution is the principal requirement to enable recolonization of the leopard population in the Caucasus ecoregion (Bleyhl et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our Kernel density analysis showed that female leopards were vulnerable to illegal killing at younger ages (1–6 years), whereas males showed a relatively similar mortality pattern in all age groups (0–10 years) (Figure 5a–d). This may indicate a potentially serious threat of leopard killing to species survival in Iran as the survival of adult females is a vital determinant of population self‐maintenance in big cats (Bleyhl et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, habitat degradation and climate change may put the native fauna at a competitive disadvantage against potential and already‐established invasive species (Foley 2005, Bellard et al 2013). Likewise, rewilding apex predators may be unsuccessful in a policy context that does not regulate poaching (Bleyhl et al 2021), and riparian habitat restoration may be inefficient when pollution sources are not eliminated first. Quantifying whether stressors affect biodiversity additively or synergistically requires improved environmental data, including past time series when studying legacy effects (Semper‐Pascual et al 2021) and future scenarios to inform decision‐making.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Typically, spatiotemporal data are particularly scarce for rare species that often are of high conservation concern. Recent studies show promise for using habitat and demographic proxies in such cases (Bleyhl et al 2021). Additionally, we see great potential for extending available time-series data through emerging new sensor and genetic techniques and approaches that will improve our ability to document biodiversity dynamics and patterns but will also provide a more complete, holistic picture of ecosystem restoration (Pimm et al 2015).…”
Section: Data Challengesmentioning
confidence: 99%